Positron emission tomography study of regional brain metabolic responses to a serotonergic challenge in major depressive disorder with and without comorbid lifetime alcohol dependence - Sher, Leo (2007)
This is the first study contrasting regional glucose metabolic rate (rCMRglu) responses to a serotonergic challenge in major depressive disorder (MDD) with and without comorbid alcohol dependence. In a university hospital, patients with MDD without a history of alcohol dependence (MDD only) and patients with MDD and comorbid alcohol dependence (MDD/ALC) were enrolled in this study. Subjects with comorbid borderline personality disorder were excluded. A bolus injection of approximately 5 mCi of (18)fluorodeoxyglucose was administered 3 h after the administration of placebo or fenfluramine. We found an anterior medial prefrontal cortical area where MDD/ALC subjects had more severe hypofrontality than MDD only patients. This area encompassed the left medial frontal and left and right anterior cingulate gyri. This group difference disappeared after fenfluramine administration. The fact that the observed group difference disappeared after the fenfluramine challenge suggests that serotonergic mechanisms play a role in the observed differences between the groups.